Mitigasi Bencana Pesisir Melalui Penanaman Mangrove Pada Program Kosabangsa di Desa Uwedikan Kecamatan Luwuk Timur, Kabupaten Banggai, Sulawesi Tengah - Rosmaniar Gailea; Muhammad Jufri; Bakhrani Rauf; Muhammad Afief Mubayyin; Darmawang Darmawang; Rahmansah Rahmansah; Syamsurizal Syamsurizal; Putri Indah Mayangsari; Ahmad Ridho Ramadani; Serina Serina; Ismail Ismail (Institut Pertanian Bogor, 2026)
Mangrove forest rehabilitation is essential to mitigate the impact of abrasion and mangrove ecosystem degradation. Mangrove planting activities with the community of Uwedikan Village, Luwuk Timur Subdistrict, Banggai Regency, were carried out as part of the Kosabangsa Program to support the development of the area’s potential as a Tourism Village. The aim of mangrove planting activities on Togong Island is to prevent coastal abrasion disasters on Togong Island. This community service program was conducted collaboratively between the Muhammadiyah University of Palu and the Uwedikan Village community, involving two groups: the Culinary Pokdarwis Nyiur Melambai Group (CPNMG) and the Teluk Balean Fishermen Group (TBFG), each consisting of 20 members. The activities included socialization, technical training, planting practice at target locations (Togong Island and Balean Island), and monitoring and evaluation The result of activity showed that performance of the training technical planting was classified as moderate (score 43,93) for CPNMG and score for TBFG is 29,38. A total of 750 mangrove seedlings consisting of Rhizophora mucronata, Rhizophora apiculata, and Avicennia marina were obtained from the Watershed Management Center (BPDAS) of Palu-Poso. The planting of seedlings was carried out from October 2024 in coastal areas affected by abrasion (covering 75 m x 10 m), with a planting distance of 1 x 1 m.